ACCEPTANCE OF GRIEF AND CHANGES IN FAMILY DYNAMICS IN THE FILM “BILA ESOK IBU TIADA”: A STUDY OF HERMENETICS - Chaesar, Ari Suryawati Secio; Tarigan, Nurul Husna; Asmara, Trinata; Wulandari, Wina; Pasaribu, Gumarpi Rahis (LUMBUNG AKSARA, 2025)
This study examines the acceptance of grief and changes in family dynamics shown in the film "Bila Esok Ibu Tiada" by Rudy Soedjarwo. The film focuses on the emotional journey of a family facing the loss of a mother, raising a deep theme of how each family member goes through the process of accepting grief. Using a hermeneutic approach, the study explores the different stages of grief identified by Kübler-Ross, including denial, anger, bargaining, depression, and acceptance, to show how the characters interact and cope with loss. The results of the analysis show that the film not only depicts the grief of loss, but also the far-reaching impact on relationships between family members, where the experience of grief can create conflict and strengthen bonds. The journal provides insights into the representation of grieving experiences in cultural contexts, and how film can serve as a medium for understanding and reflecting on the complex dynamics in family life after loss.